INVALIDITY AND UNRELIABILITY OF ECONOMIC MEASURES OF HAPPINESS - MACKONIS, ADOLFAS (Politologija, 2012)
Happiness economics studies economic and social factors that determine or are related to happiness. Happiness economics results are intended to inform economic and social policy. This article examines the feasibility and expediency of economic measures of happiness. It argues that economic measures of happiness are not valid in the sense that happiness is immeasurable phenomenon and that the measures are not reliable in the sense that the established level of happiness is not going to be correct. The invalidity is implied by the subjective theory of value and the unreliability, in turn, is implied by the invalidity. Happiness economics invokes assumptions that are false: happiness is not subject to be measured in a cardinal scales of measurement and to be intersubjectvely aggregated. Every individual scale of happiness can be only ordinal and these individual orders cannot be aggregated into intersubjective order due to the lack of intersubjective definition of happiness and due to the impossibility of aggregation of subjective preferences into an intersubjective rank. The validity of economic measures of happiness is further undermined by their unreliability: there is no common definition of happiness; different cultures do not have the same con cept of happiness as we want to measure it; different cultures are prone to different valuation of happiness; personal valuation of happiness is relative and prone to be context sensitive; people do not always adequately assess their perceptions; demonstrable preferences do not necessarily match the real preferences that are revealed during the choice of an actual action. Moreover, the intention to use happiness economics results to inform economic and social policy meet a moral problem. Happiness economics, through policy decisions, can transfer to the public a particular definite understanding of happiness instead of allowing spreading different possible alternative understandings of happiness.